Understanding perception of women entrepreneurs toward employees with reference to quality of work life balance (QWLB). (4th July 2021) - Patil, Prachita; Deshpande, Yogesh
Abstract: The significance of managing an employee's work life balance (WLB) has been increased clearly over the past 20 years . Two major issues of life, work and family are important parameters for women to cooperate as an entrepreneur. Here as a researcher, I aim to explore the WLB of women with employees comparing each parameter as a whole. A survey of 80 women entrepreneurs is taken to determine the issues of quality of work life balance (QWLB) in accordance of women working as an entrepreneur and their perception toward employees. A systematic stratified sampling is done to illustrate the work-life scale between startups and established women entrepreneurs and comparing their type of firm as a single proprietorship, working with spouse and with partners. The generated data were subjected to standard statistical procedures, such as analysis of variance (ANOVA) and t-test of significance. Each of the statements possessed adequate reliability and validity. This study would be helpful for management consultants, academicians, and for entrepreneurs, human resource professionals to understand various QWLB issues faced by Indian Women Entrepreneurs.